Criminal Liability for Triangle-Scheme Fraud in Motorcycle Buying and Selling (Study of Surabaya District Court Decision) - Nurloise Viano; Yuli Yuliana (Fakultas Syariah INSURI Ponorogo, 2026)
Technological advancements have fueled complex cybercrimes, including the “triangular scheme” fraud in online transactions. This scheme introduces a novel issue: the emergence of dual victims (sellers and buyers) simultaneously harmed by perpetrators acting as fictitious intermediaries. This study aims to analyze the application of criminal elements in the Surabaya District Court Decision No. 2051/Pid.B/2025/PN—Sby and to identify obstacles to its enforcement. Using a normative legal method, this study found that the elements of Article 378 of the Criminal Code (KUHP) have been satisfied. However, the finding highlights a legal gap between the application of the Criminal Code and the ITE Law; the judge adjudicated the case under conventional criminal law and disregarded the ITE Law on the dissemination of misleading information, even though electronic means are central to the modus operandi. This gap risks creating a jurisprudential vacuum and exacerbating evidentiary challenges, which are often hindered by the volatility of digital evidence and the anonymity of perpetrators’ identities. This study underscores the need for the integrated application of the Criminal Code and the ITE Law, coupled with strengthened digital forensic capabilities among law enforcement, to ensure legal certainty and comprehensive protection for victims.